The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13063-020-04328-9
|View full text |Cite
|
Sign up to set email alerts
|

Retaining participants in community-based health research: a case example on standardized planning and reporting

Abstract: Background: Effective strategies for participant retention are critical in health research to ensure validity, generalizability and efficient use of resources. Yet standardized guidelines for planning and reporting on retention efforts have been lacking. As with randomized controlled trial (RCT) and systematic review (SR) protocols, retention protocols are an opportunity to improve transparency and rigor. An RCT being conducted in British Columbia (BC), Canada provides a case example for developing a priori re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…establishing a rapport, regular follow-up interviews) could be effective strategies. 42 We also identified that number of years since recruitment was associated with increased odds of not responding to the survey (Supplementary Table 2), suggesting that efforts to engage more longstanding members of the NCMH cohort will be particularly important.…”
Section: Mental Health Worse During Covid-19 Pandemicmentioning
confidence: 87%
“…establishing a rapport, regular follow-up interviews) could be effective strategies. 42 We also identified that number of years since recruitment was associated with increased odds of not responding to the survey (Supplementary Table 2), suggesting that efforts to engage more longstanding members of the NCMH cohort will be particularly important.…”
Section: Mental Health Worse During Covid-19 Pandemicmentioning
confidence: 87%
“…After assessing inclusion and exclusion criteria, 97 papers reporting on 42 trials were included in the narrative synthesis, of which 27 trials were included in the meta-analyses (online supplemental appendix 5). 15 35–130 Online supplemental appendix 3 displays the outcomes and scales reported by each study and those included in the meta-analyses. Online supplemental appendix 6 shows the ongoing studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 42 trials, 38 were individual RCTs,37 38 44–49 54–77 79–122 124–129 and 4 were cluster RCTs15 35 36 39–43 50–53 78 123 130 (table 2). Thirty-three trials were conducted in HICs44–49 54–67 69–77 79–97 100 103 105–108 111–119 121 122 125 126 128 and eight were conducted in LMICs (Pakistan, Bangladesh, South Africa, Columbia, Jamaica, Brazil, India and Zambia) 15 35–38 41–43 50–53 68 78 96 98 99 101 102 104 109 110 120 123 124 127 129 130…”
Section: Resultsmentioning
confidence: 99%
“…First, pregnant women who missed ultrasound examinations were from poorer households and more frequently smoked. Attrition is a common issue in cohort studies, with a more successful follow-up among better-off and healthier participants (46) . Even though 78 % of those eligible were included in this study and no significant association was observed between UPF consumption and wealth index or smoking, a role for these factors in affecting fetal size is recognised (47) .…”
Section: Discussionmentioning
confidence: 99%